Streams pollution in a luxury tourism municipality in the Serra da Mantiqueira (Southeast Brazil) - Katayama, Fernando Shiguero [UNESP]; Nunes, Laís Samira Correia; Camargo, Antonio Fernando Monteiro [UNESP] (FapUNIFESP (SciELO), 2024)
Aim: Our aim was to analyze the limnological characteristics of streams located in a luxury tourism municipality in the Serra da Mantiqueira (Southeast Brazil). Methods: We analyzed water physical and chemical variables of six sampling sites located in three streams of the Sapucaí-Guaçú River Basin along the urban area of the municipality of Campos do Jordão and one sampling site in the Rio da Prata stream, as a reference location not impacted by urban pollution (São Paulo, Brazil). We measured some physical and chemical variables of the water and analyzed the concentration of nutrients (forms of N and P) in the streams close to the basin’s sources (Sites 1, 2 and 3), within and downstream of the urban area (sites 4 and 5), downstream of the municipality’s Wastewater Treatment Plant (WWTP) (Site 6) and the reference location (Site 7). To find out whether there were differences in limnological variables among the sampling sites we used the Analysis of Variance (ANOVA). To order the sampling sites according to the variation in their limnological characteristics we applied a Principal Component Analysis (PCA). Results: Our results showed that sites 1, 2 and 3, although close to the sources, presented limnological changes in relation to the reference location (Site 7) due to urban occupations in their surroundings. The sampling sites 4 and 6 are the most polluted due to urbanization and the discharge of effluents from the WWTP, respectively. The stretch between these two locations (Site 5) proved to be less polluted due to the autodepuration process. Conclusions: We concluded that the streams in the Sapucaí-Guaçú River Basin are polluted, although at different levels. The urban area of Campos do Jordão causes pollution of the streams in its surroundings due to surface runoff and the discharge of untreated sewage due to the lack of access to sewage services for a large part of the population. The absence of tertiary treatment at the WWTP leads to pollution of the stream after the release of its effluent.
Poluição em riachos em um município de turismo de luxo na Serra da Mantiqueira (Sudeste do Brasil)
Keywords: Campos do Jordão; organic pollution; treated effluents; urbanization; Wastewater Treatment Plant (WWTP)